Model psikologi komparatif ketidaksetaraan jumlah pembagian sumber daya: Studi pada Macaca fascicularis - Dwi Atmoko Agung Nugroho; Dondin Sajuthi; Sri Soepraptini Mansjoer; Entang Iskandar; Huda Shalahuddin Darusman (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2021)
This study aims to promote Macaca fascicularis as a comparative psychology model in finding the root and solution of resource inequity by exploring inhibitor effect on refusal behavior, acceptance, and aggression toward the feed distribution numbers in six pairs of female long-tailed macaques. We observed the frequency of refusal behavior, acceptance, and aggression toward the distribution of red grape with a ratio of: a) 1:1, 0:2, 1:3 without environmental inhibitors (with an opened-aclyric tray) and b) ratios 1:1 with an environmental inhibitor (with a transparent restriction box) in 60 trials per condition. The sample size was N = 10. Non-parametric statistical analysis of Wilcoxon Signed-Rank Test showed that 1:1 ratio with environmental inhibitor produces a lower response of refusal behavior compared to 1:3 without inhibitor. It produced a lower response of aggression compared to other ratios. It produced a greater acceptance compared to other ratios. These long-tailed macaques do not accept the equity conditions except with environmental inhibitors. Based on this fact, we conclude that long-tailed macaques are a good spontaneous model for the comparative psychology of inequity.